Phylogenomics of the bumblebee catfishes (Siluriformes: Pseudopimelodidae) using ultraconserved elements - Silva, Gabriel S. C. [UNESP] (2021)
Neotropical catfishes of the family Pseudopimelodidae comprise 53 species allocated to seven genera widely distributed in South America from northwestern Colombia and Venezuela to Argentina and Uruguay. Intergeneric relationships based on morphology-based phylogenies are conflicting, and the interspecific relationships remain incipient. We conducted the first molecular phylogeny of the family by analyzing sequence data from ultraconserved elements (UCEs) of the genome for 33 specimens of Pseudopimelodidae and 19 related taxa. Phylogenetic relationships were accessed by concatenated matrices using Bayesian inference and, maximum likelihood, and the coalescent approach by a species tree analysis. The phylogeny with 868 UCE loci and 906,689 bp strongly support the monophyly of Pseudopimelodidae, and the arrangement of two major subclades herein classified as subfamilies Pseudopimelodinae and the newly proposed Batrochoglaninae. Pseudopimelodinae is composed by Cruciglanis sister to Pseudopimelodus and Rhyacoglanis, whereas the new subfamily Batrochoglaninae is composed by Cephalosilurus and Lophiosilurus as sister to Batrochoglanis and Microglanis. Pseudopimelodinae is supported by five morphological synapomorphies and Batrochoglaninae supported by three such synapomorphies. The results of this study will surely guide future research aiming to delimit and describe species within the monophyletic groups.